Mechanisms for flowering plants to benefit arthropod natural enemies of insect pests: Prospects for enhanced use in agriculture - Lu, Zhongxian; Zhu, Ping-Yang; Gurr, Geoff M.; Zheng, Xusong; Read, Donna M. Y.; Heong, Kong Luen; Yang, Ya-Jun; Xu, Hongxing (Wiley, 2014)
Reduction of noncrop habitats, intensive use of pesticides and high levels of disturbance associated with intensive crop production simplify the farming landscape and bring about a sharp decline of biodiversity. This, in turn, weakens the biological control ecosystem service provided by arthropod natural enemies. Strategic use of flowering plants to enhance plant biodiversity in a well‐targeted manner can provide natural enemies with food sources and shelter to improve biological control and reduce dependence on chemical pesticides. This article reviews the nutritional value of various types of plant‐derived food for natural enemies, possible adverse effects on pest management, and the practical application of flowering plants in orchards, vegetables and field crops, agricultural systems where most research has taken place. Prospects for more effective use of flowering plants to maximize biological control of insect pests in agroecosystem are good but depend up on selection of optimal plant species based on information on the ecological mechanisms by which natural enemies are selectively favored over pest species.